What can we learn from the past?—A pediatrician's view. (December 2016) - Eriksson, Margareta; Bennet, Rutger
Abstract: When the tuberculosis epidemic reached its peak in central Europe in the 1900s (not until the 2000s in sub-Saharan Africa), both contained and disseminated tuberculosis was mainly regarded as a childhood disease. From 1920, before the use of the Bacillus Calmette–Guérin (BCG) vaccine and the possibility of drug treatment, there was a drastic decline in the rate of tuberculosis incidence in the Western world. In 1970, the case rate had declined in Sweden from 500/100, 000 individuals to 1/100, 000 individuals. We recently studied childhood tuberculosis in the Stockholm area from 1971 to 2015. During this period the case rate had increased from 1/100, 000 individuals to 8/100, 000 individuals. A major contributing factor has been increased immigration and, more recently, from high incidence countries. While there are very few cases in Swedish children whose parents are also born in Sweden, the case rate is still high in foreign-born children, for example, 450/100, 000 foreign-born Somali children. At the beginning of the past 45 years, sentinel (infected in Sweden with no known source person) cases were a reality but they are rarely seen today. This may be attributed to better organization, contact tracing, screening, and early diagnosis in the adult population.